Analysis of Delays in Delivery of Exported Goods at Freight Forwarder PT Arindo Jaya Mandiri Semarang - Anugraheni, Esti Ayu; Kurniawati, Nurul Imani (Asian Journal of Logistics Management, 2024)
PT. Arindo Jaya Mandiri is a freight forwarder company. PT. Arindo Jaya Mandiri must provide the best service to meet customer needs. However, the process of sending export goods often experiences delays so that consumers complain. This research was carried out with the aim of knowing the flow of export goods delivery and the critical points that cause delays, knowing the supporting and inhibiting factors, and knowing the Fault Tree Analysis method. The method uses a qualitative descriptive approach. The research results show that the export goods delivery flow starts from the stuffing flow to the payment flow. However, obstacles that influence such as human error, document discrepancies, natural disasters, and the fleet. The Fault Tree Analysis method is used to analyze the causes of delays in delivery of the highest priority goods, namely the fleet. The conclusion is that PT. Arindo Jaya Mandiri sends export goods without any reference so the company only carries out work according to custom. Delivery of export goods is carried out by creating Standard Operating Procedures